Arbitration in foreign investment: The need for equitable treatment between the investor and the host state - Mimoso, Maria João (2018)
This study aims to analyse the phenomenon of arbitration as a paradigm in solving emerging controversies of foreign investment. We will present their benefits and demonstrate their contribution to greater legal certainty in economic relations. This article explores the legal relevant concepts under a strictly conceptual methodology, preparing future research to be developed under more developed comparative law methodologies. The review of national and international literature and jurisprudence will reveal the importance of arbitration in the field of international economic relations, presenting it as an alternative dispute resolution. Globalization imposes new forms of investment protection and appeals to other forms of dispute settlement, primarily to prevent, among other problems, the possible bias of the recipient country's investment tribunals. Characterization of foreign investment, its regulatory sources, their characteristics and the need for intervention of an entity capable of resolving disputes between the parties involved: State investor reception; Investor (of a nationality other than the latter); State of the investor's nationality, and sometimes a ‘subsidiary’ local foreign investor. The ICSID (International Settlement of Investment Disputes) arbitration as a means of resolving investment litigations covered by bilateral treaties (BIT) and investment contracts calls for a delimitation of these two figures in order to clarify the scope of the arbitration under the aegis of the World Bank and to make it more secure in the view of the sovereign power of the States.